Energy Audit in a College Building – A Case Study - Mondal, S; Saha, A; Ghosh, S; Fatma, F; Fatima, M; Debsarma, P.K; Bhuinya, P; Routh, P; Roy, A (International Journal of Computer Sciences and Engineering, 2025)
For a developing country like India, scarcity of energy brings an impact in the development of the country. In India, Energy Demand is always more than the Energy Generated, due to the wastage of energy that is wasted in our daily life . In order to meet the energy need in a particular region some other region is being deprived from the Electrical Energy Supply . The monitoring of proper utilization of energy can contribute in the development of our country. Energy Audit is an analysis indicating how energy can be reduced and the study evaluate the energy consumption and to minimize the wastage of energy by implementing several techniques in our surrounding. Huge amount of energy gets wasted in industries, firms and educational institutes a huge amount of energy consumed in these area are comparatively more than that used in domestic need. The energy audit report draws the need for the organization to monitor its energy need and to reduce the demand and to make a cost effective system as it will also reduce the expense of the organization and will benefit the society as well as the organization.